SOURCE STUDIES OF LIBRARIES IN CENTRAL ASIA DURING THE "SECOND MUSLIM RENAISSANCE" (World Bulletin of Management and Law, 2023)
In the palaces of Amir Temur and his descendants there were rich libraries where unique works of the ancient world and the Middle Ages were preserved. Madrasah and khanaqakh students analyzed many books from various fields of science. In Samarkand there were rich libraries of Amir Temur and Mirza Ulugbek, in Herat of Mirza Boysunkur, Sultan Hussein Boygaro and Alisher Navoi. Authors of that time often dedicated their works to the library. For example, as Giyosiddin Koshiy noted in the introduction to his works, he dedicated them to the library of Ulugbek. Libraries not only stored various books, but also taught the art of calligraphy. Scientists in various fields have made extensive use of libraries. For example, the library of Alisher Navoi was widely used by Mirkhond, his grandson Khondamir and others. The book treasures contained manuscripts of valuable works in various fields of science. The owners of the library tried to enrich it with new works
Keywords: Library; manuscripts; education